216-13: Does higher contact force impair lesion formation at the cavotricuspid isthmus? Insights from MR-guided ablation of atrial flutter. (10th June 2016) - Chubb, Henry; Karim, Rashed; Williams, Steven; Harrison, James; Whitaker, John; Wright, Matthew; Schaeffter, Tobias; Razavi, Reza; O'Neill, Mark
Abstract: Introduction: Contact force (CF) is a key determinant of lesion formation in radiofrequency (RF) ablation. A novel MR-guided ablation system provides an insight in humans into the effect of catheter-myocardium contact upon RF energy delivery. We hypothesised that energy delivery outside of the MR-derived atrial anatomy, implying deformation of the thin atrial wall due to higher CF, would result in more efficacious lesion formation. Methods: Point-by-point RF ablation of atrial flutter was performed in 9 patients within an MRI scanner, using an MR-guided ablation system with active tracking (mean 24 lesions per patient, 35–45W, irrigated). Catheter tip position during RF delivery was recorded using an active tracking sequence (precision 0.8mm) and referenced to a 3D whole-heart dataset. Atrial scar imaging (LGE) was performed at 3 months post procedure and the ablation points re-registered to the 3D scar image using a rigid registration of the two 3D datasets. The distance between atrial wall and ablation points was calculated and atrial scar interrogated within a 3mm radius. Results: Lesion formation was significantly greater when the RF energy was delivered <10mm outside of the right atrial mesh (signal intensity 5.27 standard deviations (SD) above blood pool mean, versus 1.43 SD at >10mm (p<0.0001)). In predicting effective ablation, the negative predictive value of excessive atrial wall deformation (>10mm) was 84%, with sensitivity 93% (area under curve 0.68). Conclusion: Contrary to expectation, greater wall deformation was associated with less efficacious chronic lesion formation. The effect of higher CF on the deposition of RF energy in adjacent structures, such as lung or liver, requires further evaluation.